Supporting the Parenting Programs in Learning during the Pandemic Period through a Comprehensive Connecting Sheet - Grahita Kusumastuti; Johandri Taufan; Iga Setia Utami (The Center for Disability Studies and Services Brawijaya University, 2020)
This article discusses about the contact sheet in parenting program which is useful for supporting learning during a pandemic. Participants in this article were 17 special school teachers and parents of students. Using the seminar and workshop method, teachers and parents are trained to develop comprehensive contact sheets to support learning during a pandemic. The seminar activities presented two experts, namely special education experts and educational technology. Workshop activities were carried out for five days in a row to assist teachers in which they can be more skilled in compiling comprehensive contact sheets. The result of this training is expected to support the achievement of learning objectives during the COVID-19 pandemic as well as on weekdays later through online and non-online home learning activities.